Redesenho dos processos da superintendência de serviços próprios - Marques, Michele Regina D’Ávila (Universidade do Vale do Rio dos Sinos, 2013)
This work consists in the Management Plan preparation, whose primary goal is to redesign the processes of the Superintendence of Own Services, by connecting the inputs and outputs to the macro process of the Cooperative as well as verifying the viability and adherence for software unification/optimization to the service management, preserving customer data integrated to other Organization flows. In order to consolidate the best Project Management Practices, the work was constituted following the nine knowledge areas, focusing on the processes such as billing and paying of member doctors of Laboratory services, oncology and Home Care services were chosen, since they represent a great impact in the Organization operations, given this circumstance.
Keywords: Gestão de projetos; Processos; Gerenciamento; Project management; Processes; Management